2021
DOI: 10.1002/aenm.202100666
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lithium Dendrite Formation in Lithium Metal Batteries via Regulated Cation Transport through Ultrathin Sub‐Nanometer Porous Carbon Nanomembranes

Abstract: Suppressing Li dendrite growth has gained research interest due to the high theoretical capacity of Li metal anodes. Traditional Celgard membranes which are currently used in Li metal batteries fall short in achieving uniform Li flux at the electrode/electrolyte interface due to their inherent irregular pore sizes. Here, the use of an ultrathin (≈1.2 nm) carbon nanomembrane (CNM) which contains sub‐nanometer sized pores as an interlayer to regulate the mass transport of Li‐ions is demonstrated. Symmetrical cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 86 publications
2
49
0
Order By: Relevance
“…Figure S3 shows the Li plating/stripping reaction at a current density of 0.5 mA/cm 2 and an areal capacity of 0.5 mAh/cm 2 . Interestingly, the results clearly indicate that the overpotential for Li plating/stripping is approximately 25 mV and the overpotential is almost constant for more than 100 h at around 30 mV, resulting in the obtained values being in good agreement with the existing scientific literature evaluated using carbonate electrolytes at room temperature. A slight change in polarization during cycling is relatively negligible when compared to the polarization effect observed in the voltage profiles of Figure a. This Li plating/stripping behavior at high temperature certainly confirms that the Li metal is reversibly involved in electrochemical reactions without any detrimental parasitic reaction in the presence of the ionic liquid electrolyte.…”
Section: Resultssupporting
confidence: 82%
“…Figure S3 shows the Li plating/stripping reaction at a current density of 0.5 mA/cm 2 and an areal capacity of 0.5 mAh/cm 2 . Interestingly, the results clearly indicate that the overpotential for Li plating/stripping is approximately 25 mV and the overpotential is almost constant for more than 100 h at around 30 mV, resulting in the obtained values being in good agreement with the existing scientific literature evaluated using carbonate electrolytes at room temperature. A slight change in polarization during cycling is relatively negligible when compared to the polarization effect observed in the voltage profiles of Figure a. This Li plating/stripping behavior at high temperature certainly confirms that the Li metal is reversibly involved in electrochemical reactions without any detrimental parasitic reaction in the presence of the ionic liquid electrolyte.…”
Section: Resultssupporting
confidence: 82%
“…In recent years, extensive attempts have been made to develop high-performance Li metal batteries, including modifying liquid electrolytes, 7,8,55 engineering a solid electrolyte interface (SEI), 9,10 using solid-state electrolytes, 11–13,56 constructing Li-based alloys, 14–16 improving the wetting ability of the separator, 17–19 and designing hosts for the Li metal anodes. 20–23,57,58 Among these strategies, designing 3D hosts for Li metal anodes can provide a large contact area between the electrode and the electrolyte to reduce local current densities and relieve the volume change during Li plating/stripping, which can result in excellent electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Rajendran et al recently demonstrated the potential of a carbon nanomembrane to regulate ion transport through a Celgard membrane. 16 Other investigations focus on the disruption of dendritic growth along the anode surface. Zhang et al 17 suggest that simply maintaining consistent pressure in the battery cell can suppress dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…The nanotowers have “lithiophilic” properties which encourage uniform ionic deposition on the anode surface. On the other hand, Rajendran et al recently demonstrated the potential of a carbon nanomembrane to regulate ion transport through a Celgard membrane …”
Section: Introductionmentioning
confidence: 99%